Freedom, work and organizations in the 21st century: Freedom for whom and for whose purpose?. (October 2022) - Lindebaum, Dirk; den Hond, Frank; Greenwood, Michelle; Chamberlain, James A; Andersson, Lynne
This article critically interrogates the meaning of freedom and its current and potential relationship with social relations in and around work as introduction to this special issue. This interrogation is vital given neoliberalism's evaluative promise for more individual and corporate freedom, while concurrently limiting the conditions for the experience/expression of freedom of workers. Consequently, there are concerns about working for "private governments", workers being subject to electronic surveillance, and workers increasingly caught up in structural disadvantages (i.e. precarious work) that contribute to growing unfreedom. Rather than reproducing abstract principles around freedom, this article and special issue advance a contextually sensitive emergence of freedom. We explicate this emergence as (i) alternative experiences of freedom, (ii) alternative conceptions of freedom, and (iii) alternative modes of organizing. To inspire future research, we extend these themes to suggest that treating freedom (i) as pluralist/relational and (ii) as having the capacity for world-making has meaningful implications for how work is organized and for whose benefit. We advocate an explicit turn to non-neoliberal values (e.g. collectivism, solidarity, human dignity, respect, and recognition) to enable more relational versions of freedom that can serve as a basis for freedom as world-making at work and in society.